Influence of Local Revenue, Balance Fund, and Other Legitimate Regional Income on Regional Expenditure In Banjarbaru City - Rusty Nofian; Dewi Rahayu; Rizali Rizali (Syntax Literate, 2021)
The implementation of regional autonomy policy is supported by the balance fund between the central and local governments, the balance fund consists of the General Aloksi Fund, the Special Allocation Fund and the Revenue Sharing Fund. In addition to the balance fund the local government can utilize the original revenue of the region from the Tax Proceeds, Regional Levy, The Results of The Management of Destroyed Wealth and Other Legitimate Regional Income. The purpose of the study to find out if the local native income, balance fund, other legitimate regional incomes have a significant effect on local spending in banjarbaru city government. The method used in research is quantitative method. The research sample uses secondary data taken from the 2005 – 2018 ApBD Realization Report. The data analysis tool used in this study is Multiple Linear Regression. Test data with classic assumption tests and hypothesis tests with determination coefficient tests, F-tests, and t-tests. The study used four variables tested, namely Regional Expenditure as dependent variable (Y) and Regional Native Income (X1), Balance Fund (X2), Other Legitimate Regional Income (X3) as independent variables. The results showed the Regional Original Revenue, Balance Fund, and others- Other Legitimate Regional Revenues simultaneously have a significant effect on Regional Expenditure and partially only the Balance Fund has a significant effect while the Regional Native Income and Other Legitimate Regional Revenues do not significantly affect regional spending in Banjarbaru City. The implementation of regional autonomy resulted in the region being given the responsibility to take advantage of opportunities to explore the potential of the region to support the financial capabilities of the region.